Queer Jewish Strangers in American Popular Culture: Life Between Assimilation and Otherness - Karp, Amy Tziporah (Lexington Books, 2023)
Queer Jewish Strangers in American Popular Culture: Life Between Assimilation and Otherness explores LGBTQIA+ Jewish American identity in the United States and the queer Jewish stranger figures who live in between incorporation and estrangement. Amy Tziporah Karp establishes that despite the near-ubiquitous portrayal of Jewish American assimilation as a finished project completed in the wake of World War II in academic disciplines and throughout popular culture, many LGBTQIA+ Jewish figures in contemporary popular culture inhabit stranger positionalities. In these stranger spaces, characters are forced to either perpetually attempt to assimilate or inhabit this interstitial stranger identity that is often viewed as a nowhere, or homeless, space. Those who pursue assimilating endlessly try to fit in to no avail, such as Jenny Schecter from Showtime's popular The L Word who is ultimately killed off on the show, possibly murdered by her LGBTQIA+ community of friends. Karp shows that those who attempt to make a home in a stranger positionality align themselves with other estranged and othered peoples, such as characters throughout Sarah Schulman's novels, and that this constitutes an ethical stance against the ways in which assimilation often inadvertently supports the workings of violent hegemonies in the United States.